{(x-y) sqrty = sqrtx / 2), ((x + y) sqrtx = 3sqrty):}?

{(x-y) sqrty = sqrtx / 2), ((x + y) sqrtx = 3sqrty):}?
Anonim

תשובה:

# (x, y), (- sqrt2, -1 / sqrt2), (sqrt2,1 / sqrt2), (- (3sqrt3) / 4, -qqrt3 / 4), ((3sqrt3) / 4, sqrt3 / 4)) #

הסבר:

# (x = y = 1/2 sqrt (x / y)), (x + y = 3 sqrt (y / x)):} #

לכן

# (x = 2-y ^ 2 = 3/2), ((x-y) / (x + y) = 1 / 6x / y): #

פתרון עבור # x, y # אנחנו מקבלים

# (x, y), (- sqrt2, -1 / sqrt2), (sqrt2,1 / sqrt2), (- (3sqrt3) / 4, -qqrt3 / 4), ((3sqrt3) / 4, sqrt3 / 4)) #